“How Do I Stop Checking Things?” Understanding Obsessive-Compulsive Disorder from Neuropsychological Perspective - Ardian Praptomojati (Buletin Psikologi, 2019)
Obsessive-compulsive disorder (OCD) is the fourth most common mental disorder and WHO classifies it as one of the ten most disabling medical conditions. OCD patients have difficulty in controlling the disturbing thoughts accompanied by ritualistic behavior performed by the patient as a way to reduce anxiety or fear that leads to distress and significant dysfunction in their everyday life. Studies using neuroimaging techniques indicated a number of abnormal functions in the orbitofrontal cortex and caudate nuclei in OCD patients. Abnormalities in one or more neurotransmitters such as serotonin, glutamate, GABA, and dopamine were also found to be associated with the mechanism of the brain circuitry associated with OCD symptoms. Genetic factors were proven to also contribute considerably to OCD. This article is a literature study on OCD, especially from a neuropsychological perspective highlighting the recent development of various techniques and methods of study.